Al-Żahabi's Thought in Hadith (Study of Talkhīṣ Mustadrak al-Ḥākim Book) - Umar, Siddiq Aminullah; Arifuddin Ahmad; Erwin Hafid (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research explores the thoughts of al-Żahabi in the field of hadith, specifically within his book Talkhīṣ al-Mustadrak. The objective is to understand al-Żahabi's perspectives on hadith in this particular work. This literature review employs a combined approach of hadith and historical sciences. The data analysis methods include descriptive and comparative analysis. The findings reveal that al-Żahabi provided accurate scholarly commentary on the hadiths in Al-Mustadrak. For instance, he criticized a hadith authenticated by al-Hakim from the companion Sa’d bin Abi Waqqāṣ in al-Mustadrak due to its weak chain originating from Ṭalḥah bin Zaid al-Qurasyi, deemed weak by many hadith scholars. Despite this, there are instances of errors in al-Zahabi's assessments, such as in the evaluation of a hadith in the al-Mustadrak